Searching for the physiological role of glucose‐dependent insulinotropic polypeptide. (April 2016) - Holst, Jens Juul; Windeløv, Johanne Agerlin; Boer, Geke Aline; Pedersen, Jens; Svendsen, Berit; Christensen, Mikkel; Torekov, Signe; Asmar, Meena; Hartmann, Bolette; Nissen, Anne
Abstract: Glucose‐dependent insulinotropic polypeptide (GIP) was established as a gut hormone more than 40 years ago, and there is good experimental support for its role as an incretin hormone although deletion of the GIP receptor or the GIP cells or GIP receptor mutations have only minor effects on glucose metabolism. Unlike the related hormone, GLP‐1, GIP stimulates the secretion of glucagon, which in healthy individuals may help to stabilize glucose levels, but in people with type 2 diabetes may contribute to glucose intolerance. A role in lipid metabolism is supported by numerous indirect observations and by resistance to diet‐induced obesity after deletion of the GIP receptor. However, a clear effect on lipid clearance could not be identified in humans, raising doubt about its importance. The GIP receptor is widely expressed in the body and also appears to be expressed on bone cells, and experimental studies in rodent point to effects on bone metabolism. Recent studies revealed pronounced inhibitory effects of GIP on bone resorption markers in humans and suggest that GIP may be (one of the) gastrointestinal regulators of bone turn‐over. In support of this, a loss‐of‐function GIP receptor mutation in humans is associated with a marked increase in fracture risk. The lack of a reliable GIP receptor antagonist contributes to the uncertainty regarding the physiological role of GIP.